(untitled) (Sebha University Conference Proceedings, 2025)
Herbs used for a long time represent a great source of active ingredients that open up horizons for searching for new treatments against various diseases. However, with the advancement of science, drugs have been manufactured from synthetic chemical compounds that may cause side effects. This study aims to know the effect of the methanolic extract of Artemisia herba alba on blood indicators and peripheral blood film in female albino rats induced by cyclophosphamide. The results showed that the plant contains active compounds such as flavonoids, phenols, proteins, terpenes, tannins, saponins and glycosides, and does not contain racin and starch. The quantitative estimation results also showed that the extract contains a close percentage of flavonoids for both concentrations 200 and 400 ml/mg, which was estimated at 300 mg, while the percentage of phenols in the concentration 200 ml/mg was estimated at (94.05 mg), and in the concentration 400 ml/mg at (101.5 mg). Theresults of the blood indicators showed that Cyclophosphamide drug led to a significant decrease in the level of HB, WBC, MCV, MCH, MCHC and PCV for the PC group compared to the NC group (p<0.05), while a significant increase was observed for these values ​​in both groups T200 and T400 compared to the PC group. In the groups treated with wormwood extract only for the N200 and N400 groups, there was a significant decrease in MCH, MCV, MCHC and a significant increase in RBC, PCV, PLT, while no significant differences were observed for HB, WBC, RDW compared to the NC group. The results of this study also showed the presence of abnormal shapes of red blood cells, and the presence of abnormal shapes varied between groups, as it was observed in the T200 and T400 groups that they contained small numbers of deformed shapes compared to the PC group.